2022
DOI: 10.1039/d1dt04179g
|View full text |Cite
|
Sign up to set email alerts
|

Platinum thiolate complexes supported by PBP and POCOP pincer ligands as efficient catalysts for the hydrosilylation of carbonyl compounds

Abstract: Diphosphino-boryl-based PBP pincer platinum thiolate complexes, [Pt(SR){B(NCH2PtBu2)2-1,2-C6H4}] (R = H, 1a; Ph, 1b), and benzene-based bisphosphinite POCOP pincer platinum thiolate complexes, [Pt(SR)(tBu2PO)2-1,3-C6H3] (R = H, 2a; Ph, 2b), were prepared...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 83 publications
1
18
0
1
Order By: Relevance
“…Similar to other closely related pincer Pt­(II) complexes, the platinum center adopts a distorted square planar geometry. The structural parameters around the Pt center are also comparable to those of the related pincer Pt­(II) complexes with square planar geometry. , However, the Pt–Cl bond length in complex 1a is longer than that in the related POCOP complex [2,6-( t Bu 2 PO) 2 C 6 H 3 ]­PtCl ( 1c ) [2.398(3) vs 2.3865(4) Å].…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Similar to other closely related pincer Pt­(II) complexes, the platinum center adopts a distorted square planar geometry. The structural parameters around the Pt center are also comparable to those of the related pincer Pt­(II) complexes with square planar geometry. , However, the Pt–Cl bond length in complex 1a is longer than that in the related POCOP complex [2,6-( t Bu 2 PO) 2 C 6 H 3 ]­PtCl ( 1c ) [2.398(3) vs 2.3865(4) Å].…”
Section: Resultssupporting
confidence: 54%
“…We have been interested in the catalytic application of pincer-ligated group 10 metal complexes in chemical transformations. Recently, we found that platinum­(II) complexes supported by bisphosphinite POCOP or diphosphino-boryl PBP pincer ligand are efficient catalysts for the hydrosilylation of aldehydes and ketones . Very recently, in order to investigate the influence of the auxiliary ligands on the catalytic activity of the metal center, we applied POCOP pincer-ligated platinum hydride and thiolate complexes to the hydrosilylation of imines .…”
Section: Introductionmentioning
confidence: 99%
“…The crystallography data for the PBP pincer platforms in Ni-PBP and Pt-PBP are comparable to those of other related transition metal PBP pincer complexes as expected. 9,27–33 The Ni1–H2c and Ni1–H2d bond lengths (1.78(2) and 1.73(2) Å) in the complex Ni-PBP are very similar; the Pt1–H2c and Pt1–H2f bond lengths (2.08(5) and 2.06(5) Å) in the complex Pt-PBP are almost identical. The Ni1⋯B2 distance (2.2224(19) Å) is much longer than the sum of the covalent radius of Ni and B atoms (1.95 Å); the Pt1⋯B2 distance (2.470(5) Å) is also much longer than the sum of the covalent radius of Pt and B atoms (2.08 Å).…”
Section: Resultsmentioning
confidence: 95%
“…For many years, we have been working in the area of the structure, reactivity and catalytic applications of group 10 metal complexes supported by different types of pincer ligands. During our investigation, we noticed that many hydroboration and hydrosilylation of aldehydes, ketones and imines catalyzed by pincer ligated group 10 metal hydride complexes [33,34,40,44,54] can also be catalyzed by the corresponding thiolate complexes [48,49,54–57] . Most importantly, the thiolate complexes usually exhibit higher catalytic activity than the hydride complexes.…”
Section: Introductionmentioning
confidence: 87%
“…Bisphosphinite‐based POCOP pincer nickel and platinum hydride complexes [40,44] and the corresponding thiolate complexes [55,57] are all active in catalyzing the hydrosilylation of aldehydes. Diphosphino‐boryl‐based PBP pincer platinum hydride and the corresponding thiolate complexes are also active in catalyzing this type of reaction [55] .…”
Section: The Catalytic Activities Of the Thiolate And The Hydride Com...mentioning
confidence: 99%